A scalable coaxial bioprinting technology for mesenchymal stem cell microfiber fabrication and high extracellular vesicle yield. (3rd December 2021) - Chen, Jianwei; Zhou, Duchao; Nie, Zhenguo; Lu, Liang; Lin, Zhidong; Zhou, Dezhi; Zhang, Yi; Long, Xiaoyan; Fan, Siyang; Xu, Tao
Abstract: Mesenchymal stem cell (MSC)-derived extracellular vesicles (EVs) are promising candidates for regenerative medicine; however, the lack of scalable methods for high quantity EV production limits their application. In addition, signature EV-derived proteins shared in 3D environments and 2D surfaces, remain mostly unknown. Herein, we present a platform combining MSC microfiber culture with ultracentrifugation purification for high EV yield. Within this platform, a high quantity MSC solution (∼3 × 10 8 total cells) is encapsulated in a meter-long hollow hydrogel-microfiber via coaxial bioprinting technology. In this 3D core–shell microfiber environment, MSCs express higher levels of stemness markers (Oct4, Nanog, Sox2) than in 2D culture, and maintain their differentiation capacity. Moreover, this platform enriches particles by ∼1009-fold compared to conventional 2D culture, while preserving their pro-angiogenic properties. Liquid chromatography-mass spectrometry characterization results demonstrate that EVs derived from our platform and conventional 2D culturing have unique protein profiles with 3D-EVs having a greater variety of proteins (1023 vs 605), however, they also share certain proteins (536) and signature MSC-EV proteins (10). This platform, therefore, provides a new tool for EV production using microfibers in one culture dish, thereby reducing space, labor, time, and cost.